World Wide Web journal. - International WWW Conference (Sebastapol, Calif. O'Reilly, 1995)
Quarterly.
"A publication of the World Wide Web Consortium"--Cover.
Also available via the internet: World Wide Web journal (Online)
Other title: W3J.
Some issues contain the proceedings of: International World-Wide Web Conference.
Some issues have additional title.
Keywords: World Wide Web (Information retrieval system) -- Periodicals